Nonlinear Behaviour of Perforated Plate with Lining - Nandagopan, O. R.; Kumar, S. Ranjith; Rajesh, M. R.; Manoharan, K.; Nandakumar, C. G. (Defence Science Journal, 2012)
Perforated plate with lining has a construction of plate with perforation and a lining plate welded together to form a single plate. This type of plate is used as an acoustic sonar dome. Perforated plate with lining (PPL) is prone to stress concentration and subsequently such structural system falls into the large strain category. Experimental investigation on PPL is carried out in the present study to determine the static deflection of the plate. Numerical method is also followed for geometric nonlinear analysis using finite element method as an iterative interactive procedure. The deflection obtained from the numerical method is 8 per cent less than that obtained from experimental method. From numerical analysis, von Mises stress and maximum principal stress is also estimated to understanda bout the failure mode characteristics of PPL. Defence Science Journal, 2012, 62(4), pp.248-251, DOI:http://dx.doi.org/10.14429/dsj.62.927